2015
DOI: 10.1589/jpts.27.1593
|View full text |Cite
|
Sign up to set email alerts
|

Effect of space balance 3D training using visual feedback on balance and mobility in acute stroke patients

Abstract: [Purpose] The purpose of the study was to determine the effects of balance training with Space Balance 3D, which is a computerized measurement and visual feedback balance assessment system, on balance and mobility in acute stroke patients. [Subjects and Methods] This was a randomized controlled trial in which 52 subjects were assigned randomly into either an experimental group or a control group. The experimental group, which contained 26 subjects, received balance training with a Space Balance 3D exercise pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 19 publications
0
15
0
2
Order By: Relevance
“…This kind of asymmetry impairs balance, walking, and various other functions 12 ) . Balance is the ability to maintain the balance of body, and it is one of the body functions that maintains body stability, an important factor in daily life 13 ) . Balance is affected by a variety of factors, such as biodynamics, and it involves the integration of the visual system with the somatic nervous system, muscle strength, the ROM of joints, and the motor control ability of the myotonus 14 ) .…”
Section: Discussionmentioning
confidence: 99%
“…This kind of asymmetry impairs balance, walking, and various other functions 12 ) . Balance is the ability to maintain the balance of body, and it is one of the body functions that maintains body stability, an important factor in daily life 13 ) . Balance is affected by a variety of factors, such as biodynamics, and it involves the integration of the visual system with the somatic nervous system, muscle strength, the ROM of joints, and the motor control ability of the myotonus 14 ) .…”
Section: Discussionmentioning
confidence: 99%
“…In the Timed Up and Go test, the experimental group showed a statistically significantly decrease from 20.3±7.7 before the training to 18.6±5.2 after the training. Moreover, in a study by Yoo et al, both the experimental and control groups showed a significant decrease in performance time in the Timed Up and Go test, which was greater in the combined exercise group 17 , 18 ) . These findings are consistent with our study results.…”
Section: Discussionmentioning
confidence: 91%
“…Neste âmbito, podem-se destacar as observações a respeito do equilíbrio, já que esse apresenta participação crucial nas atividades rotineiras e de locomoção dos indivíduos, tornando seu processo de reabilitação essencial diante de patologias que acarretam o seu comprometimento 22,23 . Deste modo, uma considerável quantidade de estudos constata benefícios no equilíbrio de indivíduos com hemiparesia, provenientes de reabilitações que contém feedback visual 23,24 e isso pode ser explicado ao considerarmos que a informação visual fornecida, pode compensar os déficits somatossensoriais, resultando em uma melhor resposta motora 23,25 , argumentos esses que reforçam os achados adquiridos nesse estudo.…”
Section: Discussionunclassified